Synthesis, characterization and cytotoxic evaluation of chitosan nanoparticles: in vitro liver cancer model. (1st August 2016) - Loutfy, Samah A; Alam El-Din, Hanaa M; Elberry, Mostafa H; Allam, Nanis G; Hasanin, M T M; Abdellah, Ahmed M
Abstract: To evaluate the cytotoxic effect of chitosan nanoparticles (CS-NPs) on an in vitro human liver cancer cell model (HepG2) and their possible application as a drug delivery system, we synthesized water-soluble CS-NPs, investigated their properties and extensively evaluated their cytotoxic activity on the cellular and molecular levels. A human liver cancer cell line was used as a model of human liver cancer. The CS-NPs were characterized using transmission electron microscopy, Fourier transform infrared spectroscopy, and zeta analysis. The cytotoxic effects of the CS-NPs on HepG2 cells were monitored by sulforhodamine B colorimetric assays for cytotoxicity screening and flow cytometric analysis. Molecular investigations including DNA fragmentation and the expression of some apoptotic genes on the transcriptional RNA level were conducted. Treatment of HepG2 with different concentrations of 150 nm diameter CS-NPs did not show alteration of cell morphology after 24 h of cell exposure. Also, when cells were treated with 100 μ g ml −1 of CS-NPs, 12% of them were killed and IC50 reached 239 μ g ml −1 after 48 h of cell exposure. Flow cytometry evaluation of the CS-NPs revealed mild accumulation in the G2/M phase followed by cellular DNA fragmentation after 48 h of cell exposure. Extensive evaluation of the cytotoxic effect of the CS-NPs showed messenger RNA (mRNA) apoptotic gene expression (p53, Bak, Caspase3) after 24 h of cell exposure with no expression of the mRNA of the caspase 3 gene after 48 h of cell exposure, suggesting the involvement of an intrinsic apoptotic caspase-independent pathway by increasing the exposure time of 100 μ g ml −1 of the CS-NPs. The engineered CS-NPs were controlled to a 150 nm size and charges of 40 mV and a concentration of 100 μ g ml −1 revealed a genotoxic effect on HepG2 after 48 h of cell exposure through intrinsic apoptotic caspase-independent mechanisms. Further quantitative analysis on the molecular and protein levels is still required to confirm the impact of chitosan size and time on genotoxic effect before reaching a final conclusion and starting its biomedical application.